2015
DOI: 10.1016/j.ijosm.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic graduates perceptions of stress and competence – A longitudinal study

Abstract: Objective: The objective of this study was to explore osteopathy students' perceptions of occupational stress and clinical practice competence, and how these perceptions changed after six months of osteopathic practice. Participants: Students who graduated in 2010 from Victoria University's osteopathy program. Method: Participants completed one survey as final year osteopathy students in November 2010 and one survey as registered osteopaths in July 2011. The surveys were developed by drawing on previous work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Our results showed that perception of preparedness increased after 1 year of practice in the same cohort assessed in a previous study (Table 2) [13]. This result is in agreement with Subramaniam et al [12] who found that Australian osteopathic graduates felt more competent after 6 months in practice, even if this study was limited by its low response rate (27%). Interestingly, in the present study no significant difference was found between male and female osteopaths as to overall perceived preparedness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that perception of preparedness increased after 1 year of practice in the same cohort assessed in a previous study (Table 2) [13]. This result is in agreement with Subramaniam et al [12] who found that Australian osteopathic graduates felt more competent after 6 months in practice, even if this study was limited by its low response rate (27%). Interestingly, in the present study no significant difference was found between male and female osteopaths as to overall perceived preparedness.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, colleagues and employers considered osteopathy graduates only partially prepared for developing effective, patient centred treatment plans and promoting self-help [11]. In Australia, Subramaniam et al [12] found that osteopathy graduates felt underprepared in medico-legal procedures, risk management, paediatrics and prognosis and management of difficult patients. Differences in perceived preparedness were also reported among European osteopathic educational institutions (OEIs) [13, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Vaughan et al (2014) found positive scores among two Australian institutions [ 17 ]. Also in Australia, Subramaniam and colleagues (2014) [ 18 ] found that students perceived a lack of competence in several clinical areas, and their lack of preparedness was linked to increased stress during the transition from student to practitioner [ 19 , 20 ]; this may negatively impact on the effectiveness and safety of osteopathic care.…”
Section: Introductionmentioning
confidence: 99%
“…Their beliefs are crucial as they may impact both patients [20] and students' attitudes towards patients. Furthermore, finalyear osteopathy students are a population that has often been studied concerning professional identity [44], impact of language they use on patients' beliefs [45], attitudes toward psychosocial risk factors [46], clinical assessment [47][48][49], and perceived preparedness [50,51]. However, the beliefs of this specific population in a French OEI towards cLBP has to our knowledge never been evaluated.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%